하경추 편측 후관절 탈구의 초기 치료에서 폐쇄적 견인 정복 - 송경진(Kyung-Jin Song); 이수경(Su-Kyung Lee); 임종한(Jong-Han Lim); 고종현(Jong-Hyun Ko); 이광복(Kwang-Bok Lee) (The journal of the Korean Orthopaedic Association, 2013)
목적: 하경추 편측 후관절 탈구는 빠른 정복이 필요하나, 정복을 실패하는 경우가 있어 이에 폐쇄적 정복을 방해하는 인자에 대해 분석, 폐쇄적 견인 정복의 유용성과 적응증을 알아보고자 하였다. 대상 및 방법: 하경추 편측 후관절 탈구 26명(남 17명, 여 9명)을 대상으로 하였고, 평균 나이는 49세(20-69세)였다. Gardner 폐쇄적 견인 정복을 시도하였다. 후관절 잠김(locking) 정도, 추간판 탈출증, 반대측 후관절 아탈구 정도, 후관절 골절 여부를 확인하였고,손상 분절 위치, 나이 및 성별의 관계가 정복에 영향을 주는지에 대하여 분석하였다. 결과: 후관절 잠김이 50%가 넘는 경우 실패율이 높았다(p=0.039). 추간판 탈출, 반대측 후관절 아탈구 정도, 후관절 골절, 척추경 및후궁 골절은 정복에 영향이 없었다. 손상 분절 위치, 탈구 부위, 성별의 연관성은 없었고, 40세 미만에서 실패율이 높았다(p=0.043). 폐쇄적 견인 정복은 26명의 환자 중 12예(46.2%)에서 성공, 14예(53.8%)에서 실패하였다. 결론: 후관절 잠김 정도가 50% 미만에서 폐쇄적 견인 정복은 유용하며, 40세 미만, 잠김 정도 50% 이상인 경우 전신 마취하에 정복을 시도하고 적절한 수술을 시도하는 것이 좋을 것으로 생각한다. Purpose: Subaxial unilateral facet dislocation requires immediate reduction; however, cases of failure with reduction have also been reported. We analyzed the factors preventing closed traction reduction and attempted to determine the efficacy and indications of closed traction reduction. Materials and Methods: We selected 26 patients, 17 men and nine women. The average age of the patients in selected group was 49 years (20-69 years). Each patient was first treated with Gardner head traction and closed traction reduction. Each patient was checked for the degree of locking of the dislocated segment, intervertebral disc herniation, the degree of contralateral facet joint subluxation, and accompanied fracture. The effect of the location of the injured segment, age, and sex on closed reduction traction was analyzed. Results: A high rate of unsuccessful closed traction reduction was observed for patients with more than 50% locking of the dislocated facet joint (p=0.039). Intervertebral disc herniation, the degree of contralateral facet joint subluxation, facet joint fracture, and pedicle and lamina fracture were unrelated to the success of closed traction reduction. The location of dislocation and sex showed no statistically significant relevance to failure of closed traction reduction. A high rate of failure was observed for patients younger than 40 years. Of the 26 patients, closed traction reduction was successful for 12 and unsuccessful for 14. Conclusion: For patients whose degree of locking of the dislocated facet joint is less than 50%, closed traction reduction using skull traction is considered effective, however, for patients younger than 40 years or with more than 50% locking of the dislocated facet, prompt reduction under general anesthesia and subsequent appropriate surgery is considered beneficial. KCI Citation Count: 1